Living in contrasting agricultural worlds and yet experiencing similar anxieties - Knežević Hočevar, Duška (Anthropological notebooks, 2023)
The special issue Living in contrasting agricultural worlds and yet experiencing similar anxieties is one of the products of the bilateral scientific cooperation between Slovenia and the USA between 2022 and 2024, which aims to jointly reflect on how to deal with distress of people who farm. Despite the contrasting agricultural worlds, farmers and farm workers in both states are exposed to similar megatrends and pressures of modernized agriculture, which is reflected in the farm distress phenomenon, and deaths by suicide. In their contributions, the researchers from the US Midwest and Slovenia also inform the reader about the contrasting research traditions and interventions in farmer distress, and why the lack of cultural understanding of the phenomenon increases the likelihood of failure of prevailing health interventions.
Keywords: 2022-2024; agriculture; bilateral scientific cooperation; duševno zdravje; dvostransko znanstveno sodelovanje; farmer distress; farmers; health interventions; kmetijstvo; kmetje; mental health; prekomerni stres; research; Slovenia; Slovenija; United States of America; zdravstvene intervencije; Združene države Amerike; znanstveno raziskovanje